Analysis of the use of edu-learning in basic programming competencies at SMK Ketintang Surabaya in the Covid-19 Pandemic era - Khotimah, Khusnul; Marniati, Marniati; Nugroho, Agung; hadi, Abdul; Fathoni, Ali Nur (International Journal for Educational and Vocational Studies, 2022)
Learning Management System (LMS) technology is a web-based technology developed to improve the learning process through proper planning, application and evaluation in educational institutions. The use of LMS in the learning process helps facilitate e-learning because it provides educational material without time or place constraints. SMK Ketintang is a vocational high school under the auspices of the Widya Dharma Surabaya Foundation. SMK Ketintang seeks to implement edu-learning, a Learning Management Systemplatform (LMS)equipped with chat andfeatures teleconference which are used as online learning media in the era of the Covid-19 pandemic. Edu-learning was developed with the aim of being a bridge between teachers and students in organizing and implementing learning. The analysis of the use of edu-learning as anlearning medium online in the Covid-19 pandemic era has 4 (four) indicators, including: (1) ease of use; (2) delivery of information; (3) media attractiveness; (4) media features. The results of this study indicate that the level of effectiveness in using edu-learning reaches 79.5%. So it can be concluded that edu-learning is effectively used as an online learning medium in the era of the Covid-19 pandemic.